The Carmen de viribus herbarum (GDRK 64): Between Magical Pharmacology and Homeric Didactic - Overduin, Floris (Acta Classica Universitatis Scientiarum Debreceniensis, 2021)
This paper aims to assess the nature of magic and medicine in the extant fragment of the little-known Carmen de viribus herbarum (fr. 64 Heitsch), an anonymous didactic poem of considerable length (216 hexameters have been transmitted) from the third century CE. The Carmen, a poem concerned with the curative powers of some fifteen different plants, is an evident descendant of the didactic pharmacological verse tradition of Nicander of Colophon and the like, yet its method of composition, reusing large chunks of Homeric lines, is remarkable. What sets the Carmen apart from the tradition of didactic pharmacology, moreover, is its fascination with magic, a factor virtually absent from the Nicandrean legacy. Next to pharmacological knowledge it repeatedly discusses effective plants against ghosts, apparitions, and witches.